Morality in Public Policy and Law Enforcement: Preventing Human Trafficking and Protecting Personal Data in Indonesia's Digital Era (Discourse Journal on Law and Society, 2025)
The role of morality in public policy and law enforcement, especially in relation to human trafficking, is increasingly important in the digital era. This article discusses the complexity of these challenges and strategies to prevent human trafficking and protect personal data in Indonesia. A holistic approach is needed, with law enforcement paying attention to the dimensions of morality, integrity and moral courage in policy formulation. In a digital era filled with technological changes, public policy must be able to adapt to these developments while still maintaining strong moral principles. This demands a high degree of integrity from policymakers and law enforcers to not only comply with technical rules, but also ensure that their actions are driven by the desire to create a fair and safe environment for all individuals. The recommended strategies include increasing border patrols to prevent the entry of illegal immigrants, cross-border cooperation to cut off human trafficking routes, strengthening regulations related to personal data protection, and increasing public awareness about data privacy. It is hoped that cooperation between the government, institutions and society can overcome this challenge to safeguard human rights and national security.